Local Authority Liability for Flooding: Where Should Loss Fall? - Brennan, Sean (Victoria University of Wellington Law Review, 2015)
Flooding is New Zealand's most frequent natural hazard, the cost of which is outdone only by the recent Canterbury earthquakes. Local authorities are the bodies primarily tasked with protecting communities against flooding through a range of measures including physical works such as stopbanks. This article explores the extent to which a local authority can be liable in tort where those physical works fail, causing damage. Direct liability and non-delegable duties are discussed, the latter addressing whether a local authority can nevertheless be liable having outsourced the construction of flood works to independent contractors. Additionally, whether local authorities should be liable for such damage or whether individual property owners ought to protect their own interests through insurance is discussed. This article recommends that property owners should purchase private insurance, but that local authorities should remain liable at least for their own negligence.